Air Pollution and Entrepreneurship - Liwen Guo; Zhiming Cheng; Massimiliano Tani; Sarah Cook; Jiaqi Zhao; Xi Chen (Global Labor Organization (GLO), 2022)
We examine the causal effect of air pollution on an individual's propensity for entrepreneurship in China. Our preferred model, which employs an instrumental variable approach to address endogeneity arising from sorting into entrepreneurship and locational choices, suggests that exposure to higher intensity of air pollution lowers one's proclivity for entrepreneurship. We also find that industrial activity and self-efficacy mediate the relationship between air pollution and entrepreneurship. In addition, education and gender further moderate the relationship between air pollution and self-efficacy. In particular, air pollution negatively affects self-efficacy among the less-educated and females.
Keywords: J24; L26; Q53; 330; Air pollution; Entrepreneurship; China